Mediation of kinetochore-microtubule interactions through the Ndc80 complex component Hec1 - Guimaraes, Geoffry J., author; DeLuca, Jennifer, advisor; Bamburg, James, committee member; Peersen, Olve, committee member; Reddy, A. S. N., committee member (Colorado State University. Libraries, 2011)
To view the abstract, please see the full text of the document.
Keywords: kinetochore; Hec1; microtubule; mitosis; Ndc80 complex